Pipefish Locally Adapted to Low Salinity in the Baltic Sea Retain Phenotypic Plasticity to Cope With Ancestral Salinity Levels - Goehlich, Henry; Sartoris, Linda; Wagner, Kim-Sara; Wendling, Carolin C.; Roth, Olivia (Frontiers in Ecology and Evolution, 2021)
Genetic adaptation and phenotypic plasticity facilitate the migration into new habitats and enable organisms to cope with a rapidly changing environment. In contrast to genetic adaptation that spans multiple generations as an evolutionary process, phenotypic plasticity allows acclimation within the life-time of an organism. Genetic adaptation and phenotypic plasticity are usually studied in isolation, however, only by including their interactive impact, we can understand acclimation and adaptation in nature. We aimed to explore the contribution of adaptation and plasticity in coping with an abiotic (salinity) and a biotic (Vibrio bacteria) stressor using six different populations of the broad-nosed pipefish Syngnathus typhle that originated from either high (14-17 Practical Salinity Unit (PSU) or low (7-11 PSU) saline environments along the German coastline of the Baltic Sea. We exposed wild caught animals, to either high (15 PSU) or low (7 PSU) salinity, representing native and novel salinity conditions and allowed animals to mate. After male pregnancy, offspring was split and each half was exposed to one of the two salinities and infected with Vibrio alginolyticus bacteria that were evolved at either of the two salinities in a fully reciprocal design. We investigated life history traits of fathers and expression of 47 target genes in mothers and offspring. Pregnant males originating from high salinity exposed to low salinity were highly susceptible to opportunistic fungi infections resulting in decreased offspring size and number. In contrast, no signs of fungal infection were identified in fathers originating from low saline conditions suggesting that genetic adaptation has the potential to overcome the challenges encountered at low salinity. Offspring from parents with low saline origin survived better at low salinity suggesting genetic adaptation to low salinity. In addition, we identified juvenile gene expression indicated patterns of local adaptation, trans-generational plasticity and developmental plasticity in juvenile gene expression. In conclusion, our study suggests that pipefish are locally adapted to the low salinity in their environment, however, they are retaining phenotypic plasticity, which allows them to also cope with ancestral salinity levels and prevailing pathogens.